Find new ways of thinking, seeing and doing. (2nd February 2019) - Moss, Peter
Abstract : In this extract from his latest book, Alternative Narratives in Early Childhood, Peter Moss focuses on the French philosopher Michel Foucault to explore how his perspectives on power in relationships can inform reflective and innovative practice in the early years.